Analisis Perilaku Pengguna SAMSAT Digital Nasional Menggunakan Metode TAM danTPB - Intan, Sri; Fronita, Mona; Hamzah, Muhammad Luthfi; Saputra, Eki; Anofrizen, Anofrizen; Siregar, Syafril (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This study focuses on the challenge of low user behavioral intention towards the SIGNAL app, which is an important issue in digital technology adoption. To investigate this issue, research was conducted using a comprehensive framework integrating TAM and TPB methods, with six hypotheses proposed. Data were analyzed using multiple linear regression on questionnaires completed by a sample of SIGNAL users. The results of the analysis showed a significant relationship between perceived usefulness and ease of use and users' attitude towards the app, as well as a strong relationship between users' attitude and behavioral intention to use the app. These findings signify that the more users perceive tangible benefits and ease of use of the app, the more positive their attitude, which in turn drives SIGNAL's adoption intention. However, several hypotheses were not supported by the results of the analysis, including the absence of significant relationships between perceived benefits and users' behavioral intentions, as well as between subjective norms and behavioral intentions. This suggests that although users realize the benefits of the app, social factors and perceived individual control are not significant in determining usage intentions. The implications of these findings provide guidance for digital platform developers to design more effective interventions to increase the use of SIGNAL, as well as facilitate behavior change in the community.